A peculiar mixture: German-language cultures and identities in eighteenth-century North America - Stievermann, Jan; Scheiding, Oliver (Pennsylvania State University Press, 2013)
"A collection of essays that explore the transatlantic German cultures and identities of the colonial period"--Provided by publisher
Includes bibliographical references and index. - Print version record
Keywords: North America -- Emigration and immigration -- History -- 18th century; Germany -- Emigration and immigration -- History -- 18th century -- Germany -- North America; Geschichte 1700-1800; Kultur; Deutsche; Nordamerika